Sistem Informasi Akuntansi Pendapatan Sumbangan Pembinaan Pendidikan (SPP) Pada SMU XYZ - Imam Soleh Ma'rifati - AMIK BSI Purwokerto (Evolusi : Jurnal Sains dan Manajemen, 2015)
Abstract - Revenue is an important part of the financial management of an organization because the income received will be used to finance various purposes within the organization's operational activities. School as a non-profit organization memproleh income, one of which is the acceptance of SPP. As a source of revenue it needs attention and good supervision so that revenues can be more effectively so that the sources of funding for the organization can be met. Accounting information system necessary to administer the acceptance of SPP and as an aid in the control of transactions. Schools can apply the accounting information system to manage the receipt of the SPP so much better. Accounting information system of course need the information technology and accounting application program that fits the needs of the system. In this study, the authors develop these applications using web technologies (intranet). This application is a web-Driven applications that run using a browser. The research method is descriptive method and the method of data collection methods literature. The process of application development refers to the System Development Life Cycle (SDLC). The result is a web-based application for the administration of tuition at the school reception. Keywords: Accounting Information Systems, Non-profit, Acceptance SPP.